A measure of trade intensity and country market potential - Hussein, Mazlan; Hassan, Azman; Wan Ngah, Wan Azman Saini; Raja Yusof, Raja Nerina; Awang, Khairil Wahidin (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Trade is important in driving a country’s economic growth. It has also become essential to go beyond own soil as the infrastructures and communications across countries are becoming better every year. Hence it is of great importance for policy makers to be able to measure the trade intensity of a country to identify market potential. A simple ratio between export and import of trade activities demonstrates imbalanced characteristics which add up to drawbacks in term of scaling, proportionality and symmetry issues of the existing Trade Intensity (TI) measurements. As such the analysis could potentially be erroneous due to biased and skewed characteristics. In addition, the existing TI measurements focus on bilateral trade activities between countries which do not explicitly address country market potential dimension for export opportunities that change throughout times. Thus we propose an innovative new measure of trade intensity focusing on precision trade between change in import and export elements which we named as “TI Index”. It is geometrically symmetrical, proportional and scale invariant to the changes in market potential of all products and across the world market. The pinnacle of this paper is the design and construction of an innovative new TI index for possible use in measuring country market potential. The design and construction of the TI index is geometrically illustrated using a newly constructed Geometric Trade Intensity Space Box (GTISB). This TI index provides a single number that is easy to calculate, comparable and change sensitive across all products/countries combinations globally.